Gestión De Calidad Y Su Incidencia En La Mejora Continua De Los Procesos Operativos Del Departamento De Anatomía Patológica Del Hospital “Dr. Abel Gilbert Pontón” De La Ciudad De Guayaquil. - Alvarado Álvarez, Alexandra María (2015)
To be aware of the quality of the operational process and its effect on the efficiency of the Department of Pathology at the Hospital "Dr. Abel Gilbert Ponton "of the city of Guayaquil during the period 2013-2014, a study was conducted descriptive. The information collected in this study was obtained through the research tools, such as the descriptive survey of health workers who work in this area, who form the study group. The purpose of this research work is to recognize the factors of operational and administrative processes that affect the quality of the Department, so that by means of the exhibition of this line is to provide the medical staff the opportunity to renew the quality of service they provide in your work area. Because of this, the present paper is guided to workers in the area of Pathology of the hospital so that continuously improve and achieve permanently in their work within an adequate margin of security for proper performance.